EDUKASI PENCEGAHAN TINDAK PIDANA PERDAGANGAN ORANG (HUMAN TRAFFICKING) DALAM UPAYA MEWUJUDKAN KELUARGA INDONESIA ANTI TRAFFICKING DI KELURAHAN TANGKERANG SELATAN KOTA PEKANBARU - Handayani, Febri; Angrayni, Lysa; Darwis, Muhammad; Kastulani, Mohd. (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2023)
This article discusses the implementation of legal education regarding the criminal act of human trafficking as an effort to create an anti-trafficking Indonesian family. Family economic problems often cause people to look for shortcuts to make ends meet without first considering the negative effects of the actions they take. In the era of globalization which is marked by the development of digital life, new problems have emerged in society with the development of various modes of crime that need serious attention. From conventional crimes within countries, which then developed into transnational crimes, human trafficking has been categorized as a transnational crime. In implementing the Tri Dharma, universities have the task of serving dharma to the community, strengthening the community and directing the community to understand the legal aspects of human trafficking in order to strengthen the community's legal awareness in order to avoid the crime of human trafficking.